Impact of curcumin on sirtuins: A review. Issue 12 (26th August 2018) - Zendedel, Elham; Butler, Alexandra E; Atkin, Stephen L; Sahebkar, Amirhossein
Abstract: Curcumin is a bioactive phytochemical that modulates several physiological and cellular processes leading to therapeutic effects against different diseases. Sirtuins are highly conserved nicotine adenine dinucleotide‐dependent proteins that regulate the activity of target enzymes and transcription factors by deacetylation. Curcumin possesses both antioxidant and anti‐inflammatory properties and has been shown to increase sirtuin‐1 (SIRT1) by activating small molecules. Upregulation of SIRT1 by curcumin has been reported to confer protective effects against a range of neurological disorders including glutamate excitotoxicity, β‐amyloid‐induced cell death in cortical neurons, cerebral ischemic damage, and stroke. Activation of AMPK and SIRT1 by curcumin has also been noted to mediate the protective effects of curcumin against ischemia/reperfusion injury, cardiac fibrosis, diabetes, and lipid metabolism abnormalities. These protective effects of SIRT1 activation are partly mediated by the deacetylation of p53 and reduction of apoptosis. In this review, we summarize the role of SIRT1 in mediating the pharmacological effects of curcumin in several diseases. Abstract : Curcumin has several therapeutic properties, such as cell growth inhibition and apoptosis induction. Sirtuin is a highly conserved nicotine adenine dinucleotide‐dependent protein that regulates the activity of its target enzymes and transcription factors by deacetylation. Curcumin possesses both antioxidant and anti‐inflammatory properties, increasing sirtuin‐1 through activating small molecules. Therefore, curcumin may be proposed as having benefit in the treatment of cancer and inflammatory diseases.